Corrosion resistance of zinc and zinc alloys - Porter, Frawl C. (Corrosion technology (New York, N.Y.), 1994)
A cornerstone reference in the field, this work analyzes available information on the corrosion resistance of zinc and its alloys both as solid materials and as coatings on steel, detailing the corrosion resistance of zinc in atmospheric, aqueous, underground and chemical environments. Corrosion Resistance of Zinc and Zinc Alloys illustrates the numerous benefits of zinc and duplex coatings and presents practical case histories of their use.